Peran Panti Asuhan Dalam Meningkatkan Kepercayaan Diri Pada Anak Panti Asuhan Putra Muhammadiyah Lubuk Basung - Eldina Fitri; Yeni Afrida (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine the extent of the contribution of the orphanage at the Putra Muahmmadiyah Lubuk Basung Orphanage to the development of children's self-confidence through a study of the orphanage phenomenon. By utilizing documentation and observation, interviews and qualitative methods, this research seeks to obtain a comprehensive understanding of the social realities related to the development of self-confidence in children in orphanages. The expected result of this research is to increase understanding and knowledge, especially those related to children's self-confidence. The findings of this research show the efforts made by orphanage administrators to instill self-confidence in children, enable them to voice opinions, provide guidance and direction, involve them in various activities, equip them with education and skills, and uphold their rights. child. discipline so that they can achieve achievements they should be proud of. These efforts take the form of lecture exercises carried out after every evening prayer, carrying out weekly morning education activities and participating in community activities.